Threading holder based on axial metal cylinder pins to reduce tap risk during reversion instant - Fernández-Lucio, P.; Gil Del Val, Alain; Plaza, S.; Pereira, O.; Fernández-Valdivielso, A.; López de Lacalle, L.N. (Alexandria Engineering Journal, 2023)
Internal thread profiles are used widely in manufacturing processes with the aim of assembling/disassembling different components during maintenance activities from the aeronautics sector until common industrial parts. The threading process is one of the last operations carried out to obtain those components, and consequently, it is an operation of high added value. Threading is a complex operation that must carefully synchronize the rotation with the feed movements to avoid tool breakage during the instant of tapping reversion stage. In order to avoid this risk, several toolholders were developed present in the literature but deficiencies in terms of stability and productivity. Therefore, in this work, a new toolholder is proposed in which the common springs used to mitigate the lack of perfect synchronization between rotation and feed movements are replaced by elastic metal pins achieving a torsional compliance toolholder. The results show that the use of the proposed toolholder implies not only a productivity increase but also a surface integrity improvement as well as a stress reduction that the cutting tap is subjected and thus, achieving a substantial improvement in the current tapping processes. In particular, the use of the proposed toolholder implied a 75% reduction of the maximum stress achieved in the reversal instant, improving 20% tool life with an increase of 30% cutting speed. Therefore, the use of the proposed toolholder implies a substantial improvement in the current tapping processes.
Keywords: difficult-to-cut tapping; tapping; tapping reversion instant; toolholder; Scopus; JCR